2021
DOI: 10.3390/md19020111
|View full text |Cite
|
Sign up to set email alerts
|

Using Bacillus subtilis as a Host Cell to Express an Antimicrobial Peptide from the Marine Chordate Ciona intestinalis

Abstract: Ciona molecule against microbes-A24 (CiMAM) isolated from the marine chordate Ciona intestinalis is an antimicrobial peptide. To generate CiMAM-expressing transgenic Bacillus subtilis, we constructed a plasmid expressing recombinant CiMAM (rCiMAM) and introduced it into B. subtilis. Transgenic strains C117 and C166 were selected since they were able to highly and stably express rCiMAM. We studied the bactericidal activity of pepsin-digested extracts from rCiMAM-expressing strains against freshwater and euryhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Quite recently, Lee et al . (2021) reported that the antibacterial activity driven by the transgenic B. subtilis strains expressing recombinant CiMAM, which is an AMP originated from marine chordate, displays a higher competence against halophilic pathogens specifically. In this study, based on the results obtained from the bactericidal activity, the equivalent to the efficacious dose of Tetracycline against marine pathogen V. parahaemolyticus of CiMAM‐expressing C117 strain (Lee et al ., 2021) and lactoferricin‐expressing P263 strain (in this study) was 47 and 193 ng, respectively, suggesting that transgenic B. subtilis P263 strain exhibited a stronger bactericidal activity in seawater environment than that of CiMAM‐expressing C117 strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, Lee et al . (2021) reported that the antibacterial activity driven by the transgenic B. subtilis strains expressing recombinant CiMAM, which is an AMP originated from marine chordate, displays a higher competence against halophilic pathogens specifically. In this study, based on the results obtained from the bactericidal activity, the equivalent to the efficacious dose of Tetracycline against marine pathogen V. parahaemolyticus of CiMAM‐expressing C117 strain (Lee et al ., 2021) and lactoferricin‐expressing P263 strain (in this study) was 47 and 193 ng, respectively, suggesting that transgenic B. subtilis P263 strain exhibited a stronger bactericidal activity in seawater environment than that of CiMAM‐expressing C117 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently, Lee et al (2021) reported that the antibacterial activity driven by the transgenic B. subtilis strains expressing recombinant CiMAM, which is an AMP originated from marine chordate, displays a higher competence against halophilic pathogens specifically. In this study, based on the results obtained from the bactericidal activity, the equivalent to the efficacious dose of Tetracycline against marine pathogen V. parahaemolyticus of CiMAM-expressing C117 strain (Lee et al, 2021) and lactoferricin-expressing P263 strain (in this study) was 47 and 193 ng, respectively, suggesting that transgenic B. subtilis P263 strain exhibited a stronger bactericidal activity in seawater environment than that of CiMAM-expressing C117 strain. Therefore, we conclude that the use of transgenic B. subtilis P245 and P263 strains able to produce large amounts of AMPs can both effectively kill pathogenic bacteria and mitigate the excessive use of the antibiotics, thereby reducing their harmful effects on the aquatic environment, including the elimination of antibiotic-resistant bacterial strains generated in fish and shellfish farm.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Another new molecule, a Ciona molecule against microbes-A24 (CiMAM), was described by Lee et al [ 10 ] as an alternative to the antimicrobial peptide that was isolated from the marine chordate Ciona intestinalis , using a microorganism generally recognized as safe (GRAS), Bacillus subtilis , as a host cell. The CiMAM maintained its bactericidal activity, even in a very high salt and ion environment, making the application of recombinant CiMAM-expressing transgenic B. subtilis strains a promising candidate to protect marine fish and shellfish from halophilic bacterial infection.…”
mentioning
confidence: 99%